Jaw Manipulation Using Ultrasound-Guided Inferior Alveolar Nerve Block for Trismus in Temporomandibular Disorders - Yuki Kojima; Ryozo Sendo (Case Reports in Dentistry)
Temporomandibular disorders are a group of disorders with symptoms that include pain and clicking sounds in the temporomandibular joint and restricted mouth opening. For the treatment of temporomandibular disorders with trismus, herein, we suggest a new approach: “jaw manipulation using the ultrasound-guided inferior alveolar nerve block technique.” A woman in her 60s developed temporomandibular disorders and presented with severe trismus owing to pain in the temporomandibular joint. Ultrasound-guided inferior alveolar nerve block was performed with ropivacaine, which relieved the pain in the patient. Furthermore, we performed jaw manipulation for trismus. Since the analgesic effect lasts for 3 days, self-training can be performed while the pain is relieved. After five sessions of “jaw manipulation using the ultrasound-guided inferior alveolar nerve block technique,” trismus significantly improved in this patient. Ultrasound-guided inferior alveolar nerve block can be effective in relieving temporomandibular disorder-related pain and trismus.